Avaliação da proteção induzida pela imunidade treinada mediada pela cepa vacinal BCG contra a infecção pela bactéria patogênica Brucella abortus - Ana Carolina Valente Santos Cruz de Araujo (2020)
Trained Immunity is the immunological memory phenomenon related to the innate immune system. This phenomenon is triggered by an inducing stimulus that promotes cellular changes at the epigenetic, transcriptional and functional levels. In this regard, the Bacillus Calmette-Guérin (BCG), contained in the tuberculosis vaccine, has been shown to be an efficient inducer of Trained Immunity, reprogramming innate immune cells for faster and more effective immune response after a second unrelated stimulus. Among these cells, macrophages are essential phagocytes in the combat against different pathogens. Brucella abortus is one of the main etiological agents of Brucellosis, an infectious and systemic zoonosis, responsible for generating significant losses for Brazilian economy. This pathogen presents several immune evasion mechanisms and targets host’s macrophages as its main replicative niche. In this study, we used the BCG Moreau vaccine strain in order to generate C57BL/6 bone-marrow-derived macrophages (BMDMs) able to respond to Brucella abortus infection. BCG-mediated Trained Immunity protected RAG-/- mice against B. abortus lethal challenge in vivo. Moreover, previously vaccinated C57BL/6 and RAG-/- mice demonstrated reduction in B. abortus bacterial load in the spleen, 7 and 15 days post-infection. Trained Immunity in C57BL/6 mice resulted in in vitro generated BMDMs with greater production of IL-6 and IL-1β, greater CD40 and MHC-II molecules expression on cell surface and, enhanced control of bacterial replication after challenge with B. abortus. Prior to infection with B. abortus, BCG-trained macrophages showed remarkable activation of the mTORC1 pathway and elevated levels of NLRP3 inflammasome receptor transcripts when compared to naïve macrophages. Our findings allow us to suggest that the non-specific effects triggered by BCG Moreau enhanced the innate immune system activity, mainly in macrophages, which are mediators of the observed protection against B. abortus infection. Trained Immunity represents a new approach from the perspective of immunological memory and this work contributes to the understanding of this phenomenon, which can assist in future biotechnological applications and the development of heterologous vaccines.